Peningkatan Pengelolaan Data Karyawan Menggunakan Sistem Informasi E-SDM pada Koperasi Syariah BMT IM Jateng - Syaiful Amrial Khoir (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
The need to process data and information quickly has become a widespread phenomenon and is very important to support various fields of human work. Many work sectors are now switching from manual methods to computerized systems in order to improve work results. Especially in financial institutions such as savings and loan cooperatives, computerized systems are vital considering the very large number of transactions every day. For example, the BMT Insan Mandiri Cooperative recently developed a management information system to manage employee data. The hope is that this system can improve the management of employee data owned by cooperatives. However, problems arose when cooperative HR staff were not used to using the information system, which caused difficulties in collecting employee data through the system. Therefore, there needs to be training to increase the use of HR management information systems (E-SDM). This training will be integrated into the community service program by way of practicum. The aim is for cooperative managers to use the management information system properly to improve employee data management in the cooperative.